2016
DOI: 10.4103/0259-1162.176403
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous analgesia with opioids versus femoral nerve block with 0.2% ropivacaine as preemptive analgesic for fracture femur: A randomized comparative study

Abstract: Background and Objective:Femoral fractures are extremely painful and pain invariably worsens on any movement. Anesthesia for fracture femur surgery is usually provided by spinal block. This study was undertaken to compare the analgesic effects of femoral nerve block (FNB) using nerve stimulator with 0.2% ropivacaine (15 ml) and intravenous (I.V.) fentanyl before patient positioning for fracture femur surgery under spinal anesthesia.Materials and Methods:A prospective, randomized, double-blind, comparative stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Full-text articles were excluded with no comparison (n = 4), no comparison of interest (n = 6), different interventions (n = 9), no relevant outcome measure (n = 12), and review articles (n = 4). Ten studies [10][11][12][13][14][15][16][17][18][19] were ultimately included for qualitative and quantitative synthesis. single centers in Italy [16], Ireland [18], Pakistan [10], India [12,13,15,17,19], Nepal [14], and Thailand [11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Full-text articles were excluded with no comparison (n = 4), no comparison of interest (n = 6), different interventions (n = 9), no relevant outcome measure (n = 12), and review articles (n = 4). Ten studies [10][11][12][13][14][15][16][17][18][19] were ultimately included for qualitative and quantitative synthesis. single centers in Italy [16], Ireland [18], Pakistan [10], India [12,13,15,17,19], Nepal [14], and Thailand [11].…”
Section: Discussionmentioning
confidence: 99%
“…Two [10,12] of the studies recruited a majority of females for FNB. Four [11,15,17,19] studies recruited equal numbers of the two sexes, and one [13] study provided no information on sex. Three trials [10,11,16] reported the time from trauma to surgery, and averages ranged from 2.3-15.6 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations